Al-gertani v. Bosnia and Herzegovina. (2016) - Unknown
Abstract : 261 Human rights — Right to life — Prohibition of torture and cruel, inhuman or degrading treatment or punishment — Right to liberty and security of person — Whether States Parties ensuring the extension of Covenant rights to all persons within their territories without distinction — Whether arrested persons being informed of reasons for arrest — Entitlement of persons deprived of their liberty to challenge lawfulness of detention before a court — Whether alien lawfully within the territory of a State Party being expelled in pursuit of a decision reached in accordance with law — All persons equal before courts and tribunals — Entitlement to a fair and public hearing by a competent, independent and impartial tribunal established by law — Prohibition on arbitrary or unlawful interference with privacy, family and home — Recognition and protection of the family as the natural and fundamental group unit of society — Right of every child to such measures of protection as are required by his status as a minor — International Covenant on Civil and Political Rights, 1966, Articles 6, 7, 9, 13, 14, 17, 23 and 24 — Remedy for violation — United Nations Human Rights Committee